Organizing for War in Canada, 1812-1814: The U.S. Army Experience - Olinger, Mark (Ontario History)

(untitled) (The Ontario Historical Society, 2012)
This article examines the organizing, training, and equipping of the U.S. Army during the War of 1812. When the war began, Congress raised forces by expanding the Regular Army, authorizing the use of volunteers, and calling out the militia. In organizing the required forces regimental organizations were used. The lack of trained personnel and the short duration of campaigns would result in these regiments being organized into ad hoc brigades and divisions, which varied widely in strength from as small as in the hundreds to a few thousand. Most of the units had little training and were poorly equipped, creating largely ineffective fighting forces. Against this background, the types of regiments, brigades and divisions the U.S. Army employed in the campaigns against Upper and Lower Canada, a comparison of the effectiveness of the militiamen and regulars, and the significance of the battles in the Niagara River area, will be covered.